Modified Folk Sandstone Classification - Amin-Rasouli, Hadi (Sulaimani Journal for Pure and Applied Sciences, 2016)
The Folk’s method of sandstone classification has been very commonly used by many sedimentologists. However, problems may be encountered using this method of classification. The problems include the size of matrix, the components used in the poles of triangular diagram, inability to classify some sandstone samples and the fact that the description of sandstone and its position in the diagram do not always match. In the proposed modified Folk classification, all of these problems have been resolved, the boundary between grain and matrix size is chosen to be 0.0625 mm, and if the matrix is 10 to 50%, wacke term is preferred. To use this term, it is enough to add wacke to sandstone name after omitting the arenite, if it was.
Keywords: Folk classification,Modified Folk,Sandstone; Matrix